Answer
3 quarters
Step-by-step explanation:
Equation B: 4y = 2 − 4z
Step 1: −4(y) = −4(4 − 2z) [Equation A is multiplied by −4.]
4y = 2 − 4z [Equation B]
Step 2: −4y = 4 − 2z [Equation A in Step 1 is simplified.]
4y = 2 − 4z [Equation B]
Step 3: 0 = 6 − 6z [Equations in Step 2 are added.]
Step 4: 6z = 6
Step 5: z = 1
In which step did the student first make an error?
Step 1
Step 3
Step 4
Step 2
Answer:
b
Step-by-step explanation:
B) 2
C) -0.5
D) -3
Answer:
12π ≈ 37.68
Step-by-step explanation:
The Circumference formula is C=πd
Since the radius is 6, the diameter will be 12
Now just plug it in
C = 12π
Answer:
37.68
Step-by-step explanation:
C = 2πr
2 x 3.14 x 6